The Application of Behavioral Conditioning Procedures to the Problems of Quality Control - Adam, Everett E.; Scott, William E. (Academy of Management Journal, 1971)
Rather than only emphasizing statistical techniques to control performance quality, it is suggested that modification of performance quality may readily be understood as the behavioral consequences of psychological conditioning procedures. Operant conditioning principles are reviewed and implications are related to the industrial quality control problem. An experimental investigation provides an example of the quality control problem viewed as a behavioral change phenomenon, where the agent for change is the use of conditioning procedures.